THE MAIN GENRES OF CHILDREN'S LITERATURE IN THE HISTORICAL AND LITERARY PROCESS OF ENGLAND IN THE XIXTH AND EARLY XXTH CENTURIES - Sobirova Gulasal Madat qizi (TADQIQOTLAR, 2025)
The  main  genres  of  children's  literature  in  XIXth  and  early  XXth  century England reflect a dynamic interplay between cultural values, educational philosophies, and  artistic  expression.  This  era  laid  the  groundwork  for  contemporary  children's literature, fostering a legacy that champions creativity, empathy, and the exploration of complex themes through the lens of childhood. As society continues to evolve, so too does children's literature, but the foundational developments of this period remain pivotal in shaping its trajectory.